Coauthoring with undergraduates in writing studies: revising identities and institutions - Grobman, Laurie, editor; Greer, Jane, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2025)
This collection focused on the largely unexplored tradition of faculty/undergraduate publication and theorizes about coauthoring experiences within a variety of institutional contexts to explore the relationships between undergraduates and faculty that lead to coauthoring.--Provided by publisher.
Spaces and places of coauthoring -- Situating faculty-student coauthoring in a department of English / Joyce Kinkead and Shane Graham -- Lingering, listening, and co-creating: undergraduate writing center researchers and the ethics of coauthoring / Steven J. Corbett, Annette Vara, and Katherine Villareal -- Coauthoring the writing studies curriculum: an ongoing student-faculty partnership / Heather Thomson-Bunn and Mía Zendejas -- Cultivating boundary dwellers: coauthoring collaborative relationships with undergraduates in community engagement / Tina Le and Rachael Shah -- Models and methods of coauthoring -- Nested coauthorship: a framework for building productive undergraduate research experiences / Teresa Contino, Isabella Gomez, Leah Senatro, and Amy Lueck -- Feminist pedagogy and coauthorship: decentering meaning-making and valuing students' authentic voices / Letizia Guglielmo -- Collaborative coauthorship among graduate and undergraduate students: a horizontal, mutual mentorship model for writing projects / Jennifer Burke Reifman, Mik Penarroyo-Smith, Mikenna Modesto, and Loren Torres -- Archives as sites of collaboration: "side-by-side" coauthoring / Lynée Lewis Gaillet -- Scenes from behind the scenes: fostering reciprocal faculty-undergraduate coauthorships via feminist communities of practice / Vanessa Sohan, Jennifer Peña, Xuan Jiang, and Giovanna Rodriguez -- Consequences of and reflections on coauthoring -- Destabilizing and restabilizing hierarchies in faculty-undergraduate coauthoring / Abby M. Dubisar -- Telling our own stories: coauthoring with students to advance DEI pedagogy / Lauren S. Cardon and Brandy Martinez -- Charting a pathway from first-year composition to academic publishing / Shirley Faulkner-Springfield, Kayla Moore, and Charity Riddick-Mullen -- Creative-critical coauthoring: definition and demonstration / Sandy Feinstein, Nicolas Fay, Faith Iseman, Ashley Offenback, Christian D. Brendel, Rachel Jensen, and Jennifer Muret-Bate.
Keywords: English language -- Rhetoric -- Study and teaching (Higher); Authorship -- Collaboration; Academic writing -- Study and teaching (Higher)